Respuesta :
Under constant temperature and pressure the change in free energy (ΔG) equals the difference between the change in enthalpy (ΔH) of the system and the product of the temperature, T, times the change in the entropy (ΔS).
This is: ΔG = ΔH - TΔS
The reaction is:
2NH3(g) + 2O2(g) -> NH4NO3(s) + H2O(l)
So,
ΔGf = ΔGf of the products - ΔGf of the reactants
ΔGf products = ΔHf products - TΔS products
ΔGf reactants = ΔHf reactants - TΔS reactants
T = 298 K
ΔHf products = ΔHf NH4NO3(s) + ΔHf H2O(l) = -365.56 kJ - 285.830 kJ = -651.390 kJ
TΔSf products = TΔSf NH4NO3 + TΔSf H2O(l) = 298K (151.08 J/K + 69.91 J/k) = 65,855.02 J = 65.855 kJ
ΔGf products = -651.390kJ - 65.855kJ = -717.245 J
ΔHf reactants = 2ΔHf NH3(g) + 2ΔHf O2(g) = 2*(-46.11kJ) + 2*(0.00kJ) = -92.22 kJ
TΔSf reactants = 298k*2*(ΔSf NH3) + 298k*2*(ΔSf O2) =298k*2(192.45 J/K + 205 J/K) = 236,880.2 J = 236.880 kJ
ΔG f reactants = -92.22 kJ - 236.880kJ = -329.100 kJ
ΔGf = ΔG f products - ΔG f reactants = -717.245kJ - (-329.100kJ) = -388.145 kJ
Answer: - 388.145 kJ
This is: ΔG = ΔH - TΔS
The reaction is:
2NH3(g) + 2O2(g) -> NH4NO3(s) + H2O(l)
So,
ΔGf = ΔGf of the products - ΔGf of the reactants
ΔGf products = ΔHf products - TΔS products
ΔGf reactants = ΔHf reactants - TΔS reactants
T = 298 K
ΔHf products = ΔHf NH4NO3(s) + ΔHf H2O(l) = -365.56 kJ - 285.830 kJ = -651.390 kJ
TΔSf products = TΔSf NH4NO3 + TΔSf H2O(l) = 298K (151.08 J/K + 69.91 J/k) = 65,855.02 J = 65.855 kJ
ΔGf products = -651.390kJ - 65.855kJ = -717.245 J
ΔHf reactants = 2ΔHf NH3(g) + 2ΔHf O2(g) = 2*(-46.11kJ) + 2*(0.00kJ) = -92.22 kJ
TΔSf reactants = 298k*2*(ΔSf NH3) + 298k*2*(ΔSf O2) =298k*2(192.45 J/K + 205 J/K) = 236,880.2 J = 236.880 kJ
ΔG f reactants = -92.22 kJ - 236.880kJ = -329.100 kJ
ΔGf = ΔG f products - ΔG f reactants = -717.245kJ - (-329.100kJ) = -388.145 kJ
Answer: - 388.145 kJ
Answer:
E for Plato users
Explanation:
I took the test